Avaliação da citotoxicidade e atividade antioxidante de plantas condimentares - Matiolli, Larissa Silva [UNESP] (2014)
Plants condiments define the species used to add odor or flavor to food and is present in human food for thousands of years. Than employment in food, stand out because they have healing and therapeutic benefits, with antiinflammatory, analgesic, antitumor, antimicrobial and antioxidant. To ensure the benefits attributed to these plants, it became important to study the cytotoxicity of the same, considering the likely health risk due to erroneous and / or misuse of certain condiments plants, which may potentially cause alterations in DNA. Given the above, the present work aimed to evaluate the cytotoxic and antioxidant potential of Cinnamomum zeylanicum Breyn (Cinnamon), Origanum vulgare (Oregano), Petrosolium sativum L. (Salsa), Piper nigrum L. (Black Pepper) Zingiber officinale Roscoe (ginger) and Ocimum basilicum L. (Basil), through bioassay with Allium cepa, concluding that showed no cytotoxicity at the concentrations evaluated. And the DPPH test, Fe2 + chelating effect, FRAP test, total phenols and flavonoids has been shown that the tested plant condiments can be used as a source of natural antioxidants, flavonoid and phenolic compounds